2023
DOI: 10.1101/gr.276643.122
|View full text |Cite
|
Sign up to set email alerts
|

Active enhancers strengthen insulation by RNA-mediated CTCF binding at chromatin domain boundaries

Abstract: Vertebrate genomes are partitioned into chromatin domains or topologically associating domains (TADs), which are typically bound by head-to-head pairs of CTCF binding sites. Transcription at domain boundaries correlates with better insulation; however, it is not known whether the boundary transcripts themselves contribute to boundary function. Here we characterize boundary-associated RNAs genome-wide, focusing on the disease-relevantINK4a/ARFandMYCTAD. Using CTCF site deletions and boundary-associated RNA knoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Permanently paused states could also be caused by polymerase unbinding and CTCF capturing the RNA chain. Transcription could therefore enable CTCF to recruit RNA to CBSs and lead to an increased insulation at domain boundaries 65 . Impaired transcription by CTCF could also regulate Pol II pausing 47 , which has been linked to alternative splicing 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Permanently paused states could also be caused by polymerase unbinding and CTCF capturing the RNA chain. Transcription could therefore enable CTCF to recruit RNA to CBSs and lead to an increased insulation at domain boundaries 65 . Impaired transcription by CTCF could also regulate Pol II pausing 47 , which has been linked to alternative splicing 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies have argued that the experimentally observed large chromatin loops and non-random organization are not probable by a purely thermal process and predicted an active loop extrusion process as the potential mechanism [33,[45][46][47][48]. Several studies found supporting evidence for this idea and discovered that dynamic loop formation by cohesins is crucial for chromatin organization in the interphase and CCCTC-binding factor (CTCF) plays an essential role in maintaining TAD boundaries [27,[49][50][51][52][53][54][55][56][57]. These findings led to the emergence of a dynamic picture where, in the interphase, structural maintenance of chromosomes (SMC) complexes like cohesins (and associated proteins) extrude a loop until they encounter a CTCF barrier.…”
Section: Introductionmentioning
confidence: 99%
“…The genome in the nucleus is organized into different layers of higher architecture, ranging from nucleosome to chromatin looping, to topologically associated domains (TADs), and A/B compartments (7,8). Some TAD boundaries overlap with protein-coding genes or non-coding genes (9)(10)(11)(12). The non-coding RNA transcribed from a TAD boundary (bRNA) has been reported to strengthen TAD insulation by recruiting CTCF to the TAD boundary (9).…”
Section: Introductionmentioning
confidence: 99%
“…Some TAD boundaries overlap with protein-coding genes or non-coding genes (9)(10)(11)(12). The non-coding RNA transcribed from a TAD boundary (bRNA) has been reported to strengthen TAD insulation by recruiting CTCF to the TAD boundary (9). R loops, which are DNA:RNA hybrids, form as natural byproducts of transcription and accumulate around transcription start and termination sites (13).…”
Section: Introductionmentioning
confidence: 99%